Subcutaneous Administration of D-Luciferin is an Effective Alternative to Intraperitoneal Injection in Bioluminescence Imaging of Xenograft Tumors in Nude Mice. (18th December 2013) - Khalil, Ashraf A.; Jameson, Mark J.; Broaddus, William C.; Chung, Theodore D.; Golding, Sarah E.; Dever, Seth M.; Rosenberg, Elisabeth; Valerie, Kristoffer
Abstract : Currently, intraperitoneal (IP) injection of D-luciferin is the preferred method of providing substrate for bioluminescence imaging (BLI); however it has a failure rate of 3–10% due to accidental intestinal injection. The present study evaluates the quality of BLI after subcutaneous (SC) injection of D-luciferin and demonstrates the effectiveness of SC injection in anatomically disparate tumor models. Mice bearing luciferase-expressing tumors underwent BLI after SC or IP injection of D-luciferin. The average time to maximal luminescence was 6 min (range 5–9 min) after SC injection and 8 min (range 5–8 min) after IP injection. Within 7 minutes of injection, SC and IP routes yielded similar luminescence in subcutaneous, intracranial, tongue, and lung xenograft tumor models. In a model of combined subcutaneous and intracranial xenografts, SC injection resulted in proportional luminescence at all sites, confirming that preferential delivery of substrate does not occur. While tumors were occasionally not visualized with IP injection, all tumors were visualized reliably with SC injection. Thus, SC injection of D-luciferin is a convenient and effective alternative to IP injection for BLI in nude mice. It may be a preferable approach, particularly for tumors with weaker signals and/or when greater precision is required.